Efektivitas Program Percepatan Penurunan Stunting Di Desa Paluhakan Kecamatan Danau Panggang Kabupaten Hulu Sungai Utara - Norhidayah; Delsa Fatimah (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: Effectiveness is the success in achieving previously set goals. In the Effectiveness of the Stunting Reduction Acceleration Program in Palukahan Village, Danau Panggang District, Hulu Sungai Utara Regency, several problems were found, such as the increasing prevalence of stunting in Palukahan Village, the less-than-optimal socialization carried out during the integrated health post (posyandu) and the Supplementary Food Provision (PMT) program which was not fully targeted. The purpose of this study was to determine the effectiveness of the program and the factors that influence the Effectiveness of the Stunting Reduction Acceleration Program in Palukahan Village, Danau Panggang District, Hulu Sungai Utara Regency. The research method used is a qualitative method with a qualitative descriptive type, data collection techniques, namely observation, interviews and documentation. Determination of data sources using purposive sampling techniques, with 10 informants. Data analysis techniques use data collection, data condensation, data presentation, drawing conclusions and verification. Data credibility testing, namely increasing perseverance, triangulation, using reference materials and member checks. The results of the study indicate that the Effectiveness of the Stunting Reduction Acceleration Program in Palukahan Village, Danau Panggang District, Hulu Sungai Utara Regency is less effective as seen from the indicators: the suitability of the program with the target is less effective, the suitability with the requirements is effective, the ability of the program organizers is quite effective, community understanding is less effective, the suitability with the results is less effective, the target of the program is less effective, the program review is effective, the program evaluation is quite effective. In the effectiveness of the program there are supporting factors, namely the requirements that are in accordance with the targets and the cooperation between program implementers. On the other hand, there are factors inhibiting the effectiveness of the program, namely the lack of motivation and education on how to raise children, the lack of training for Palukahan Village cadres, and the limited village fund budget. It is recommended that the Village Consultative Body, Village Head and Palukahan Village Apparatus are expected to prioritize budget allocation